2021
DOI: 10.1186/s11671-021-03558-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanobiocide Based-Silver Nanomaterials Upon Coronaviruses: Approaches for Preventing Viral Infections

Abstract: The effectiveness of silver nanomaterials (AgNMs), as antiviral agents, has been confirmed in humans against many different types of viruses. Nanobiocides-based AgNMs can be effectively applied to eliminate coronaviruses (CoVs), as the cause of various diseases in animals and humans, particularly the fatal human respiratory infections. Mostly, these NMs act effectively against CoVs, thanks to the NMs’ fundamental anti-viral structures like reactive oxygen species (ROS), and photo-dynamic and photo-thermal abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In recent years, nanoparticles, including nano-scale metal materials, such as those made of silver, have become the focus of virucide research, due to their unique physical and chemical properties. Currently, AgNPs have been applied as therapeutics in antimicrobial ointments, long-term burn care products, and antibacterial lotions, as well as in medical dressings (commercial products approved by the FDA), including PolyMem Silver™ (Aspen), Acticoat™, Bactigras™ (Smith & Nephew), Tegaderm™ (3M), and Aquacel™ (ConvaTec) [ 14 , 15 , 16 , 17 ]. Silver nanoparticles (AgNPs) are silver clusters with a size of 1–100 nm, formed through nano-crystallization of elementary silver using nano-technology.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nanoparticles, including nano-scale metal materials, such as those made of silver, have become the focus of virucide research, due to their unique physical and chemical properties. Currently, AgNPs have been applied as therapeutics in antimicrobial ointments, long-term burn care products, and antibacterial lotions, as well as in medical dressings (commercial products approved by the FDA), including PolyMem Silver™ (Aspen), Acticoat™, Bactigras™ (Smith & Nephew), Tegaderm™ (3M), and Aquacel™ (ConvaTec) [ 14 , 15 , 16 , 17 ]. Silver nanoparticles (AgNPs) are silver clusters with a size of 1–100 nm, formed through nano-crystallization of elementary silver using nano-technology.…”
Section: Introductionmentioning
confidence: 99%
“…AgNP's main functionality is preventing the binding between host cell and main protease, probably by destroying the active sites of viruses. 86 Jeremiah et al found that AgNPs with a diameter of 2−15 nm can inhibit extracellular SARS-CoV-2 within 1 and 10 ppm concentrations. 87 Surgical and common masks, impregnated with antiviral NPs, can be an effective approach in the prevention of SARS-CoV-2.…”
Section: Combat Of Sars-cov-2mentioning
confidence: 99%
“…One of the important reasons why AgNPs have interested researchers is that they are not likely to be noncytotoxic in oral and dermal exposure at a dose of 2000 mg/kg in the rat model. AgNP’s main functionality is preventing the binding between host cell and main protease, probably by destroying the active sites of viruses . Jeremiah et al found that AgNPs with a diameter of 2–15 nm can inhibit extracellular SARS-CoV-2 within 1 and 10 ppm concentrations …”
Section: Combat Of Sars-cov-2mentioning
confidence: 99%
“…There are currently a variety of preventative tools on the market. In this regard, nanotechnology offers new opportunities for the development of COVID-19 prevention approaches that offer high sterilization with low doses, no side effects, user-friendliness, and longer life is its most important features [ 46 , 47 , 48 ]. The following is the use of nanomaterials as surface disinfectants, applications in PPE, and delivery systems for the development of prophylaxis vaccines.…”
Section: Preventionmentioning
confidence: 99%